A comparison of cognitive therapy, applied relaxation and imipramine in the treatment of panic disorder. - Clark, D; Salkovskis, P; Hackmann, A; Middleton, H; Anastasiades, P; Gelder, M (1994)
Recent studies have shown that cognitive therapy is an effective treatment for panic disorder. However, little is known about how cognitive therapy compares with other psychological and pharmacological treatments. To investigate this question 64 panic disorder patients were initially assigned to cognitive therapy, applied relaxation, imipramine (mean 233 mg/day), or a 3-month wait followed by allocation to treatment. During treatment patients had up to 12 sessions in the first 3 months and up to three booster sessions in the next 3 months. Imipramine was gradually withdrawn after 6 months. Each treatment included self-exposure homework assignments. Cognitive therapy and applied relaxation sessions lasted one hour. Imipramine sessions lasted 25 minutes. Assessments were before treatment/wait and at 3, 6, and 15 months. Comparisons with waiting-list showed all three treatments were effective. Comparisons between treatments showed that at 3 months cognitive therapy was superior to both applied relaxation and imipramine on most measures. At 6 months cognitive therapy did not differ from imipramine and both were superior to applied relaxation on several measures. Between 6 and 15 months a number of imipramine patients relapsed. At 15 months cognitive therapy was again superior to both applied relaxation and imipramine but on fewer measures than at 3 months. Cognitive measures taken at the end of treatment were significant predictors of outcome at follow-up.